Alternative Powertrains and Fuels in Heavy Non-Road Mobile Machinery and Their Future Expectations - A Review - Pesonen, Jarkko; Prinz, Robert; Ovaskainen, Heikki; Kauranen, Pertti; Poikela, Asko; Kärhä, Kalle (Springer Nature, 2025)
Purpose of the Review This literature review focused on studies on alternative powertrains and fuels of non-road mobile machinery (NRMM) during the last 15 years and investigated their future potential and expectations. The goal was to evaluate different alternative powertrains based on previous research and highlight the possibilities and challenges of each technology. Additionally, the aim was to conduct a comprehensive overview about the technology development phase of alternative powertrains. Recent Findings This review covered a total of 115 studies consisting of hybrid, full-electric, biofuels, biogas, and hydrogen solutions. The results highlighted that hybrid and full-electric technologies have the greatest potential to replace conventional diesel engines in the future. The main challenges identified were battery reliability and high technology costs. Regarding biofuel, biogas, and hydrogen, the benefits were mainly lower emissions while the challenges were high costs and low production. Full-electric and hydrogen powertrains were found to reach zero local emissions during operations, while compared to diesel, repair and maintenance caused less emissions of 36–46% during the life cycle with full-electric and hydrogen solutions. With hybrid, biofuels, and biogas powertrains, the emission reduction potential ranged from 37 to 81% during operations and 36–66% during the entire life cycle. The highest Technology Readiness Levels (TRLs) were identified for hybrid and full-electric technologies in industrial machinery (6.9–7.4). The lowest measurable TRL (2.5) was with biogas powered construction machinery. The TRLs of biogas and hydrogen of forest machinery were excluded from this review due to the lack of research. Summary Alternative powertrains can eventually replace diesel engines, if the challenges with implementation, production, and reliability are solved. Furthermore, the benefits of electric and renewable technologies/fuels are unambiguous from the emission reduction and energy efficiency perspectives. Consequently, we recommend that future research focus especially on the implementation of alternative technologies as well as the improvement of the manufacturing infrastructure.
Keywords: hybrid; electrification; renewable fuels; biofuels; biogas; hydrogen; technology readiness level (TRL)